2008
DOI: 10.1136/gut.2007.131136
|View full text |Cite
|
Sign up to set email alerts
|

A problem-oriented approach to liver disease in oncology patients

Abstract: The disciplines of oncology, clinical pharmacology, and hepatology have seen rapid growth in their respective literatures that deal with new antitumour agents; pharmacokinetics, pharmacodynamics and pharmacogenomics of cancer therapies; and the liver as a key organ in metabolism of these therapies as well as a frequent target of toxicity. The challenge for physicians caring for oncology patients is to integrate an understanding of this literature with practical considerations of how to prevent, diagnose and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 98 publications
0
31
0
Order By: Relevance
“…In the present study, the activities of AST, ALT, and ALP are increased in the serum which is considered a marker of liver damage. Hepatic dysfunction was the most common regimen-related toxicity reported in patients treated with CP and total body irradiation [37]. Hepatic tissues were the primary sites for the microsomal activation of the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the activities of AST, ALT, and ALP are increased in the serum which is considered a marker of liver damage. Hepatic dysfunction was the most common regimen-related toxicity reported in patients treated with CP and total body irradiation [37]. Hepatic tissues were the primary sites for the microsomal activation of the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…CP administration under different conditions and doses has been demonstrated to be an excellent model to produce the syndromes of both oxidative stress and hepatic damage (Mathew & Kuttan, 1997;Stankiewicz et al, 2002;Sulkowska et al, 1999). Hepatic dysfunction was the most common regimen-related toxicity reported in patients treated with CP and total body irradiation (McDonald & Frieze, 2008). Hepatic tissues were the primary sites for the microsomal activation of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…McDonald et al [18] reported challenges in deciding appropriate medication dose adjustments for patients with liver disease based on the variable medication pharmacodynamics and kinetics. As seen below (Table 1), several antineoplastic agents are metabolized by the liver and contraindicated due to increased toxicity in the setting of hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%